Risk Taking by Entrepreneurs - Vereshchagina, Galina; Hopenhayn, Hugo A. (American Economic Review, 2009)
Entrepreneurs bear substantial risk, but empirical evidence shows no sign of a positive premium. This paper develops a theory of endogenous entrepreneurial risk taking that explains why self-financed entrepreneurs may find it optimal to invest in risky projects offering no risk premium. Consistently with empirical evidence, the model predicts that poorer entrepreneurs are more likely to undertake risky projects. It also finds that incentives for risk taking are stronger when agents are impatient. (JEL G31, G32, L25, L26)